Conhecimento sobre plantas medicinais entre agricultores de base ecológica da região sul do Rio Grande do Sul - Ceolin, Teila (2009)
It is among the family members that spread information about the oral habits and health care, such as the use of medicinal plants. This study aimed to analyze the transmission of knowledge related to medicinal plants among family generations and know the transmission networks of knowledge, involving ecological farmers in Southern Rio Grande do Sul. The study used a qualitative, descriptive and exploratory approach, and was conducted with 8 ecological farming families, totaling 19 respondents residing in the counties of Pelotas, Morro Redondo, Canguçu and Arroio do Padre. Data collection occurred between January and May 2009. Were used as tools a semi-structured interviews, the construction of the genogram and eco-map, observation of plants with photographic record and georeferencing. The data were analyzed and grouped into three themes: an ethnobotanical survey of medicinal plants cited by the interviewees; contextualization of farmers in study and the knowledge about medicinal plants in different family groups. Among those interviewed, 16 were women, highlighting their importance in the transmission of knowledge between family generations. The respondents cited 196 medicinal plants, some native of Rio Grande do Sul State and others exotic, and 7 elixirs. The popular name given to some medicinal plants varied between each family investigated, occurring also assigned the same name for plants of different genera. The family was referred to as the main source in the transmission of knowledge about medicinal plants, followed by women's groups and / or church community, among others. Most subjects reported first completing treatment with medicinal plants, to seek after the formal health service. Plants are used as a practice in health care among farmers who exchange their knowledge among themselves and with other community members. Nursing, in search of comprehensive care, must understand the cultural context in which the individual and his family are inserted, their care practices and the transmission networks of popular knowledge.